2009
DOI: 10.1128/jb.01004-08
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Type III Secretion System Inhibitors Block Assembly of the Shigella Type III Secreton

Abstract: Type III secretion systems (T3SSs) are essential virulence devices for many gram-negative bacteria that are pathogenic for plants, animals, and humans. They serve to translocate virulence effector proteins directly into eukaryotic host cells. T3SSs are composed of a large cytoplasmic bulb and a transmembrane region into which a needle is embedded, protruding above the bacterial surface. The emerging antibiotic resistance of bacterial pathogens urges the development of novel strategies to fight bacterial infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(109 citation statements)
references
References 45 publications
(52 reference statements)
2
106
1
Order By: Relevance
“…Thus, an extension of this procedure can complement genetic approaches such as chemical mutagenesis. Selected SAH compounds have been used to study T3S of Chlamydia and other Gram-negative bacteria (41,(53)(54)(55). These compounds inhibit chlamydial growth, development, and secretion, suggesting a role for the T3S throughout the intracellular developmental cycle (17, 18, 19-21, 23, 24, 25, 26, 56).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an extension of this procedure can complement genetic approaches such as chemical mutagenesis. Selected SAH compounds have been used to study T3S of Chlamydia and other Gram-negative bacteria (41,(53)(54)(55). These compounds inhibit chlamydial growth, development, and secretion, suggesting a role for the T3S throughout the intracellular developmental cycle (17, 18, 19-21, 23, 24, 25, 26, 56).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the T3S inhibitors block the expression of the T3SS, possibly by inhibition of LcrF, while others appear to interfere with the secretion mechanism directly. The broad-spectrum potential of the "direct" T3S inhibitors is being established, with some inhibitors showing cross-activity against Salmonella enterica serovar Typhimurium, Shigella flexneri, and Chlamydia trachomatis (20,31,40,42). Other antivirulence approaches include inhibition of individual Yop cytotoxins delivered by the T3SS or production of iron-scavenging siderophores (3).…”
Section: Identification Of Small Molecule Inhibitors Of Lcrfmentioning
confidence: 99%
“…The repression of T3S in a diverse range of pathogens suggests that there is a common, conserved target. The most conserved region of the T3SS is the basal apparatus proteins, and this region has recently been proposed to be the target of related inhibitors in Shigella flexneri (38). We noted that the results presented in the study of Veenendaal et al do not contradict our findings as these authors showed that treatment with an inhibitor decreased the amount of the basal apparatus in the membrane, suggesting that inhibition occurs at a very early stage of assembly and insertion or at the level of transcription.…”
Section: Vol 77 2009 Effect Of T3ss Inhibitors On E Coli O157 4217mentioning
confidence: 99%